Sosialisasi Kekerasan Seksual pada Perempuan dan Stunting di Desa Banjarsari Kabupaten Magelang - Maisya Khoerunnisa; Arya Saputra; Ahmad Sabiq Fanani; Luthfita Risma Aprilianda; Nurul Hasanah; Aan Anisah; Syafarotun Khasanah; Muhammad Rafi'i Khosyi; Nada Syahda Ratna Duhita; Anang Noer Faizien (Universitas Pahlawan Tuanku Tambusai, 2026)
Sexual violence, anemia, and stunting are interrelated and pose a threat to adolescent girls’ health. This community service activity aims to increase adolescent girls’ knowledge about the prevention of these three issues as well as the use of iron supplements. It was conducted in Banjarsari Village, Magelang Regency, on July 19, 2026, through a collaboration between the University of Tidar’s 48th Community Service Program (KKN) Team and Sahabat Perempuan. The methods used included interactive lectures, discussions, and QA sessions with 20 adolescent girls aged 11–17 years. The material covered gender concepts, forms of sexual violence, their relationship to stunting, anemia prevention, and the distribution of Iron-Folic Acid Tablets (IFAT). As a result, the participants showed great enthusiasm and gained an understanding of sexual violence, how to address it, and the importance of nutrition and iron-rich foods in preventing anemia and stunting. The collaboration between the university, the village, and supporting organizations contributed to the success of the activity. This awareness campaign effectively raised awareness among adolescent girls as part of efforts to foster a healthy and empowered generation.